Real-World Data on the Usage of Hemopatch® as a Hemostat and Dural Sealant in Cranial and Spinal Neurosurgery - Schebesch, Karl-Michael; Hrbac, Tomas; Jančálek, Radim; Krska, Lukas; Marquez-Rivas, Javier; Solar, Peter (Cureus, 2023)
Background and objectives Cerebrospinal fluid (CSF) leakage is a significant complication in cranial and spinal interventions. Hemostatic patches such as Hemopatch® are therefore used to support the watertight closure of the dura mater. Recently, we published the results of a large registry documenting the effectiveness and safety of Hemopatch® in various surgical specialties, including neurosurgery. Here we aimed to analyze the outcomes from the neurological/spinal cohort of this registry in more detail. Methods Based on the data from the original registry, we performed a post hoc analysis for the neurological/spinal cohort. The Hemopatch® registry was designed as a prospective, multicenter, single-arm observational study. All surgeons were familiar with the application of Hemopatch® and it was used at the discretion of the responsible surgeon. The neurological/spinal cohort was open for patients of any age if they had received Hemopatch® during an open or minimally invasive cranial or spinal procedure. Patients with known hypersensitivity to bovine proteins or brilliant blue, intraoperative pulsatile severe bleeding, or an active infection at the potential target application site (TAS) were excluded from the registry. For the posthoc evaluation, we stratified the patients of the neurological/spinal cohort into two sub-cohorts: cranial and spinal. We collected information about the TAS, intraoperative achievement of watertight closure of the dura, and occurrence of postoperative CSF leaks. Results The registry comprised 148 patients in the neurological/spinal cohort when enrolment was stopped. The dura was the application site for Hemopatch® in 147 patients (in one patient in the sacral region after tumor excision), of which 123 underwent a cranial procedure. Twenty-four patients underwent a spinal procedure. Intraoperatively, watertight closure was achieved in 130 patients (cranial sub-cohort: 119; spinal sub-cohort: 11). Postoperative CSF leakage occurred in 11 patients (cranial sub-cohort: nine; spinal sub-cohort: two). We observed no serious adverse events related to Hemopatch®. Conclusion Our post hoc analysis of real-world data from a European registry confirms the safe and effective use of Hemopatch® in neurosurgery, including cranial and spinal procedures, as also observed in some case series.
Keywords: watertight closure; cranial; dura mater; infratentorial; neurosurgery; supratentorial; csf fistula; spinal; csf leakage; hemopatch®